Cover Image. (12th August 2020) - Xiao, Chuanxiao; Hacke, Peter; Johnston, Steve; Sulas‐Kern, Dana B.; Jiang, Chun‐Sheng; Al‐Jassim, Mowafak
Abstract : The cover image is based on the Research Article Failure analysis of field‐failed bypass diodes by Chuanxiao Xiao et al., https://doi.org/10.1002/pip.3297 .